51.7k views
4 votes
Simplify the following expression

7-5/6 × 7-7/6

User Esben
by
5.9k points

1 Answer

5 votes


\longrightarrow{\blue{ 0 }}


\sf \bf {\boxed {\mathbb {STEP-BY-STEP\:EXPLANATION:}}}


7 - ( (5)/(6) * 7) - (7)/(6)


= 7 - (35)/(6) - (7)/(6)

Since the denominators are unequal, we find the L.C.M (lowest common multiple) for the denominators.

The L. C. M is 6.

Now, multiply the L.C.M. with both numerator & denominator.


= (7 * 6)/(1 * 6) - (35)/(6) - (7)/(6)

Now that the denominators are equal, we can add/subtract them.


= (42- 35 - 7)/(6)


= (42 - 42)/(6)


= ( 0)/(6)


= 0


\red{\large\qquad \qquad \underline{ \pmb{{ \mathbb{ \maltese \: \: Mystique35♛}}}}}

User Amresh
by
5.6k points